Exploring the functional and corrosion behavior of friction stir welded NiTi shape memory alloy. (November 2019) - Mani Prabu, S.S.; Perugu, Chandra S.; H.C., Madhu; Jangde, Ashutosh; Khan, Sohel; Jayachandran, S.; Manikandan, M.; Kumar, P. Ajay; Kailas, Satish V.; Palani, I.A.
Highlights: Tool wear was observed during friction stir welding of NiTi alloy. Tungsten inclusions have altered the composition of the weld center. The weld has showed good thermomechanical properties. The corrosion resistce of NiTi alloy has reduced after welding. Abstract: The friction stir welding was proved to be a promising process to weld NiTi shape memory alloy with adequate mechanical strength and retention of shape memory effect. In this work, the tool wear during welding and the compositional change in the weld cross section has been evaluated. The tensile cyclic behavior for different strain percentages has been investigated. Interestingly, the thermomechanical behavior of the weld was studied using electrical actuation. The actuation was carried out at different current and the actuation temperatures were corroborated with phase transformation temperature range measured using differential scanning calorimetry. A maximum displacement of 17.8 mm was recorded at the actuation current of 5 A. The electrochemical corrosion testing has been performed to understand the corrosion behavior of the friction stir welded NiTi. The weld has exhibited a lower corrosion resistance than the base metal as seen from the lower breakdown potential of 250 mV and a higher current density of 1.5 × 10 −4 mA/cm 2 .